Prostate cancer which affects an elderly man is a feature of senescence (cellular) — a biology phenomenon - Drewa, T.; Jasinsk, M.; Marszalek, A.; Chlosta, P. (Experimental Oncology, 2010)
The aim of this paper was to present late-life form of the prostate cancer, which differs from its aggressive counterpart that affects men between 55–65 years old and younger. The differences can be found in carcinogenesis risk factors, cancer biology and finally patients’ survival. The most important is that these two clinical (age-related) forms of the prostate cancer are still undistinguishable in clinico-pathology reports and patients bearing different diseases are offered the same treatment. Potential mechanisms leading to development of the late-life clinically indolent prostate cancer are discussed. It seems that the key abnormalities are proteins involved in control of regenerative potential and cell senescence.